Staff training as correlate of workers’ productivity in selected service industries in Osun state, Nigeria. (2009)
Training is a process of developing and improving skills that are related to performance. Many studies have been carried out on the relationship between training and productivity of workers but none has been carried out on the correlation of training on the individual indices of productivity and workers productivity. It is against this background that this paper investigate the correlation of training on indices of workers productivity. The expost facto research design was used for the study. The random sampling technique was used to select three hundred respondents from three service industries in Osun State. A structured questionnaire tagged “Staff Training and Workers Productivity Questionnaire — STWPQ” with reliability coefficient of r =. 85 was used to collect data. The finding showed that staff training correlated positively and significantly with workers’ productivity (r -.99; p < 0.05). That increased morale at work (r = .934; P<0.05), time management (r = .974; P<0.05), reduction in rate of absenteeism (r = .969; P < 0.05) were highly and positively correlated with training hence increase in workers’ productivity. The study recommended that a training department, that is autonomous of the personnel department, should be created in every organization so as to train and prepare workers for future position and promote productivity through reduction in the rate of accidents, absenteeism and improved service delivery.